Emprendimiento artesanal y el desarrollo sostenible de la comunidad nativa Bora de Iquitos 2024 - Alvan Flores, Erick Enrique (2025)
This research study aims to determine the relationship between artisanal entrepreneurship and sustainable development in the native Bora community of Iquitos for the year 2024. With a basic, descriptive level approach and a non-experimental design, a sample of 100 was selected. people and a questionnaire was used to collect the necessary information. The results showed that artisanal entrepreneurship in the native Bora community of Iquitos is at a regular level (29%), because they sometimes seek and use emerging technologies in their production process. Regarding sustainable development, this was also rated as regular (28%), since collaborations between community members to strengthen the local economy occur occasionally. Finally, a strong and significantly positive relationship was found (rho =0.837; sig.=0.000) between artisanal entrepreneurship and sustainable development in the native Bora community of Iquitos in 2024.